Effects of Dynamic Characteristic on the 5-Storey Steel Tower with Different Orientations of Adjacent Structure - ABDUL RAHMAN, MUHAMMAD FARIS; KAMARUDIN, AHMAD FAHMY (Recent Trends in Civil Engineering and Built Environment, 2021)
There is many building in the world which are already built-in direct contact or extremely close to each other. There has dynamic interaction between two adjoining structures, and it is significantly influenced the dynamic characteristic of each other. The construction of the building which direct contact or closer to each other without sufficient separation gap or expansion joint will influenced the behavior of the building and also will modify the building dynamic characteristic in term of natural frequency and mode shape. Modal analysis had been conducted in this study to investigate the effects of dynamic characteristic on 5-storey steel tower with different orientations of adjacent structures using STAAD Pro software. 5-storey steel tower had modelled together with different orientations of adjacent structure with input properties is same with actual structure that had verified with Ambient Vibration Testing in laboratory. The dynamic characteristics of steel tower was investigated in terms of their relationship of natural frequencies, mode shape, maximum deflection amplitude and relative floor displacement amplitude. The result shows the optimum natural frequency are at level 3 for all cases. The optimum improvement has been obtained by 37.64% improvement of natural frequency for existing structure when and the worth of natural frequency is -4.4% drop from the original structure. The parametric studies were done for level 3 for every cases. It was found that the plan irregularity and unsymmetrical of structure geometry that led to complex and unexpected result.